E-Garage Sales Using Social Networks Sites Under Web 2.0 Technology. - Taher, Alhusain Mohamed Ahmed (2008)
Social Networks sites connect people for various social and but yet many SNSs lack the orientation of professional purposes on the other hand most of e-business applications today do not concern about the emotional connections among people, which has a bad effect on the business process, This study attempts to introduce garage-sales social network site that has a "Meaningful objectives" which is Customer to Customer (C2C) e-business activities, in the context of the right tool which is Web 2.0 technology. The developed e-garage sales site was evaluated through an online survey; the results showed that the users found the application useful.